Buckling of corrugated core sandwich panels - Patel, N. G. (Cranfield University, 1969)
A computer program is developed to determine the buckling stress and deflections of symmetric corrugated core sandwich panels. In the program freedom for lateral deflections at core to face-plate junction is allowed for. Provision is also made to study the effect of variation of core bend radius. A range of test specimens using four basic core configurations is designed to assess the effect of core bend radius on the buckling stress of the panel. The computer program indicates that above a certain value of core bend radius there is a marked drop in the value of critical buckling stress and a change in buckling Mode. The values of deflections at core to face-plate junctions at low buckling wave-lengths are not reliable* Due to the limited range of the experimental work, it is not possible to draw any conclusions on the effect of core bend radius on the buckling stress. The method used for determining the experimental buckling load is somewhat subjective in application, and its accuracy is difficult to assess. In general, the experimental values of buckling stresses are 15% higher than those predicted by the computer program. These discrepancies are not large when dimensional and material property variations are considered and indicate that the computer results are giving the correct trend and are conservative. Recommendations are made for : (i) Investigation of the buckling deflections at low values of buckling wave-lengths for specimens with high face-plateto-core thickness ratio. (ii) A test programme covering a wider range of specimens than that covered by the test programme in this study. and (iii) Trying out the other two methods of determining the buckling load.